The Effect of Auditor Characteristics on Audit Service Quality from an Audit Client Perspective in Libya: Proposing Conceptual Framework - Mariam Moftah Ammar; Kalsom Abd. Wahab; Izlawanie Muhammad (IISTE, 2024)
Vol 7, No 10